2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401249
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cellular Neural Networks in Semantic Segmentation

Abstract: The popularity of convolutional neural networks and deep learning based approaches has increased continuously in the past years. These methods has enabled the solution of various practical problems, but they still are not heavily exploited in the embedded domain, which requires low-power implementation of these architectures. Cellular neural networks can provide an analogue and power-efficient implementation of these networks which also enables the exploitation of non-Boolean, beyond CMOS elements such as memr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fulop et al demonstrated that CellNNs can be used for semantic segmentation 2 and image classification 22 as well. Classification accuracy of their networks is not included in Table 5, since the focus of their paper is obtaining templates for memristive continuous‐time CellNNs, while this paper is about discrete‐time CellNNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fulop et al demonstrated that CellNNs can be used for semantic segmentation 2 and image classification 22 as well. Classification accuracy of their networks is not included in Table 5, since the focus of their paper is obtaining templates for memristive continuous‐time CellNNs, while this paper is about discrete‐time CellNNs.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on deep learning have grown exponentially in the last decade. Some of the application fields that benefit from deep learning are speech recognition, 1 semantic segmentation, 2 visual object recognition, 3 and many other domains such as drug discovery 4 and genomics 5 . Krizhevsky et al 6 have made a major breakthrough in computer vision by using convolutional neural networks (CNNs) by introducing AlexNET.…”
Section: Introductionmentioning
confidence: 99%